Soils in some areas of the MacKenzie River Delta region - Pihlainen, J. A.; Brown, R. J. E.; Johnston, G. H. (National Research Council of Canada, 1956)
Soils and soil conditions typical of the delta proper are described first. Most of this information was collected during 1953, but data obtained in succeeding years also are included. Soils information also is given on areas investigated on the western edge of the delta along the Husky Channel and farther north. On the eastern edge of the delta, detailed exploratory soil surveys for the Aklavik Relocation Project were carried out at two potential townsite areas approximately 35 miles east of Aklavik. Notes on soils at Kittigazuit and in the Caribou Hills, are also included. Wherever it may prove helpful, soil information is augmented by typical aerial photographs, borehole logs, and ground photographs. : Le rapport commence par analyser les sols et les conditions de sol caractéristiques du delta proprement dit. La plupart de ces informations ont été recueillies en 1953, mais on y a inclu les données obtenues au cours des années suivantes. Les auteurs donnent également des informations sur les sols qui bordent l'ouest du delta, le long du canal Husky, et plus au nord. Sur la rive est du delta, on a effectué, pour le projet de réinstallation d'Aklavik, des levés de reconnaissance détaillés du sol à l'emplacement éventuel de deux centres urbains situés à 35 milles environ d'Aklavik. Le rapport comprend également des notes sur les sols de Kittigazuit et sur ceux des Caribou Hills. Ces données sont accompagnées, au besoin, de photographies aériennes, de diagrammes de sondage et de photographies au sol.